Proteomics Screen Identifies Class I Rab11 Family Interacting Proteins as Key Regulators of Cytokinesis. - Laflamme, C.; Galan, J.A.; Ben El Kadhi, K.; Méant, A.; Zeledon, C.; Carréno, S.; Roux, P.P.; Emery, G. (Molecular and Cellular Biology, 2017)
The 14-3-3 protein family orchestrates a complex network of molecular interactions that regulates various biological processes. Owing to their role in regulating the cell cycle and protein trafficking, 14-3-3 proteins are prevalent in human diseases such as cancer, diabetes, and neurodegeneration. 14-3-3 proteins are expressed in all eukaryotic cells, suggesting that they mediate their biological functions through evolutionarily conserved protein interactions. To identify these core 14-3-3 client proteins, we used an affinity-based proteomics approach to characterize and compare the human and Drosophila 14-3-3 interactomes. Using this approach, we identified a group of Rab11 effector proteins, termed class I Rab11 family interacting proteins (Rab11-FIPs), or Rip11 in Drosophila. We found that 14-3-3 binds to Rip11 in a phospho-dependent manner to ensure its proper subcellular distribution during cell division. Our results indicate that Rip11 plays an essential role in the regulation of cytokinesis and that this function requires its association with 14-3-3 but not with Rab11. Together, our results suggest an evolutionarily conserved role for 14-3-3 in controlling Rip11-dependent protein transport during cytokinesis.